The effect of teaching style and academic motivation on student evaluation of teaching: Insights from social cognition - Keerthigha, C.; Singh, Smita (Frontiers in Psychology, 2023)
Student evaluation of teaching (SET) is ubiquitous in higher education as a metric for assessing teachers, gaining student feedback, and informing faculty personnel decisions. It is thus imperative to examine the dimensions along which a teacher is judged. This study tested the application of the universal dimensions of social judgement (i.e., warmth and competence) in SET. A total of 108 psychology undergraduates (Mage = 23.63, SDage = 3.14) in Singapore rated a fictitious teacher (i.e., either relationship-oriented or task-oriented) based on their interactions over a programmed online chat. Participants responded to the social judgment measures of warmth and competence and rated their academic motivation. Results indicated a higher SET rating for a relationship-oriented than a task-oriented teacher. Further, student academic motivation mediated the link between teaching style and judgement of competence. The findings extend the supremacy of warmth in the context of SET, thus supporting the application of social cognition literature to educational research. In addition, the findings suggest that fostering a match in task goals between a teacher and student improves ratings of teacher competence.